2000
DOI: 10.1136/sti.76.5.355
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of trichomoniasis in rural men in Mwanza, Tanzania: results from a population based study

Abstract: Objectives:To measure the prevalence of urethral infections including trichomoniasis in rural Tanzanian men, to assess the prevalence of symptoms and signs among men with Trichomonas vaginalis, and to analyse the risk factors for trichomoniasis. Design: A cross sectional study of 1004 men aged 15-54 years in a rural community in north west Tanzania. Methods: Participants were interviewed about sexual behaviour and symptoms of sexually transmitted diseases. First fraction urine samples and urethral swabs were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
42
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 25 publications
4
42
1
Order By: Relevance
“…These findings suggest that this organism is not an important cause of urethritis in our population. This is surprising because of the high prevalence of trichomoniasis in antenatal clinic attendees in our area [11] and the high rates reported in males from most parts of Africa [3,4,21,22]. Our findings are however consistent with a recent population-based study from Tanzania where high T. vaginalis prevalence was found (11%).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These findings suggest that this organism is not an important cause of urethritis in our population. This is surprising because of the high prevalence of trichomoniasis in antenatal clinic attendees in our area [11] and the high rates reported in males from most parts of Africa [3,4,21,22]. Our findings are however consistent with a recent population-based study from Tanzania where high T. vaginalis prevalence was found (11%).…”
Section: Discussionsupporting
confidence: 75%
“…Our findings are however consistent with a recent population-based study from Tanzania where high T. vaginalis prevalence was found (11%). Only 50% of these patients were symptomatic; in most cases, with dysuria as the single complaint, and the majority had no microscopic urethritis (78%) [21]. Two other studies from Africa reported a significantly higher rate of T. vaginalis infection among patients with urethritis compared to a control group comprising men presenting to a clinic without genitourinary related complaints.…”
Section: Discussionmentioning
confidence: 96%
“…This strong biological plausibility is supported by empirical studies from Africa documenting that Trichomonas may increase HIV transmission by as much as threefold. Infection can persist at least a year, particularly in asymptomatic men (75,103), and a long-term-carrier state may result in an increased duration of elevated infectiousness for trichomoniasis and HIV (38). Moreover, although imperfect, the available data suggest that T. vaginalis is a highly prevalent infection, particularly among African-American women in urban communities of the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Our study could not confirm or outrule the presence of a visible discharge as researchers could not interfere with the providers' treatment procedures who typically did not examine patients. In studies of male urethritis in Africa, however, most men with complaints of a urethral discharge have also been found to have visible signs of discharge (Grosskurth et al 1996;Pepin et al 2001); and, conversely, urethral pathogens have also been found in men who complained of a discharge in whom a discharge was not visualized (Watson-Jones et al 2000;Pepin et al 2001), as well as in men with no complaints at all of a urethral discharge (Grosskurth et al 1996;WatsonJones et al 2000). The lack of complete diagnostics for men appropriate to our field conditions also meant that we could not study the aetiologies and roles of other STIs that are associated with urethral discharge in men, particularly Trichomonas vaginalis (TV).…”
Section: Discussionmentioning
confidence: 99%